Concept of civil society in the history of European philosophical thought - Alina Bilous (Cхід)
The article is devoted to the comprehension of the European tradition in the interpretation of civil society concept. In the proposed exploration the determinants and factors of evolution necessity of mentioned concept in the context of European theoretical field are focused